Adaptation of the Psychological Capital Questionnaire in the Educational Context in an Argentine Sample - Schönfeld, Fátima Soledad (2020)
Psychological capital is defined as a state of positive psychological development that represents the person's positive assessment of the circumstances and their probability of success based on effort and perseverance. It is a construct composed by four components or psychological strengths: efficacy, optimism, hope and resilience. It was widely described and evaluated in the workplace; however, psychological capital can be applied to other spheres of a person's life, such as education. Hence, the objective of this study is to evaluate the psychometric properties of the adaptation to the educational context of the Psychological Capital Questionnaire in the Argentinean adolescent population (N = 313). Construct validity, convergent validity (with school performance and engagement) and reliability levels are analyzed. This research provides empirical evidence that supports good levels of validity and reliability of the Psychological Capital Questionnaire in the educational context in adolescent population.